2021
DOI: 10.1159/000518255
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Future Renal Function Decline in Patients with Autosomal Dominant Polycystic Kidney Disease Using Mayo Clinic Classification

Abstract: <b><i>Introduction:</i></b> Mayo clinic classification (MCC) has been proposed in patients with autosomal dominant polycystic kidney disease (ADPKD) to identify who may experience a rapid decline of renal function. Our aim was to validate this predictive model in a population from southern Spain. <b><i>Methods:</i></b> ADPKD patients with measurements of height-adjusted total kidney volume (HtTKV) and baseline estimated glomerular filtration rate (eGFR) &#x3e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Currently, the most accepted predictor of RP is the MCC ( 16 , 17 ), as it has been shown to be the best predictor tool regardless of the CKD stage ( 17 , 18 ). In our study, 95.6% of the included patients belonged to classes 1C to 1E of MCC.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most accepted predictor of RP is the MCC ( 16 , 17 ), as it has been shown to be the best predictor tool regardless of the CKD stage ( 17 , 18 ). In our study, 95.6% of the included patients belonged to classes 1C to 1E of MCC.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies 4,24 have proposed polynomial models using age together with Mayo HtTKV class or mutation type to predict kidney function trajectories in ADPKD, we chose to retain baseline eGFR as a predictor variable due to its robust association with future eGFR. 25 However, like prior polynomial models, the precision of our model is limited, as shown by the CIs of the prediction error at follow-up (Supplemental Figure 5). This indicates that there is an ongoing challenge in developing predictive models that not only yield accurate average results for subgroups but also provide more precise predictions for individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Even with these small drawbacks, MCC has been validated as a prognostic marker of future GFR decline in several populations 2224 and has provided valuable and practical information in post hoc analysis of TEMPO 3:4 25 and HALT-polycystic kidney disease studies, 26 compared with other existing models that showed to be less applicable to clinical practice. 29 For example, application of MCC model to TEMPO 3:4 and TEMPO 4:4 studies showed that groups of patients in which tolvaptan showed clearer benefit were 1C, 1D, and 1E MCC classes, corresponding to those who underwent faster growth.…”
Section: Discussionmentioning
confidence: 99%
“…When curves were conveniently adjusted using Cox regression models including age and baseline GFR, kidney growth rate was found to be an effective predictor of future GFR deterioration in ADPKD. 20,23,24 Furthermore, this model that has been the so-called Mayo Clinic classification (MCC) has shown very interesting results when applied to Tolvaptan Efficacy and Safety in Management of Autosomal Dominant Polycystic Kidney Disease and its Outcomes (TEMPO) 3:4 25 and HALT-polycystic kidney disease studies, 26 clarifying which groups may respond more efficiently to disease-modifying treatments, with evident interest for the design of future clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation